2005
DOI: 10.1016/j.pep.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of SARS coronavirus proteins using SUMO-fusions

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV) proteins belong to a large group of proteins that is difficult to express in traditional expression systems. The ability to express and purify SARS-CoV proteins in large quantities is critical for basic research and for development of pharmaceutical agents. The work reported here demonstrates: (1) fusion of SUMO (small ubiquitin-related modifier), a 100 amino acid polypeptide, to the N-termini of SARS-CoV proteins dramatically enhances expression in Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 36 publications
3
59
0
2
Order By: Relevance
“…When used as an N-terminal carrier protein during prokaryotic expression, SUMO promotes folding and structural stability, which leads to enhanced functional production compared to untagged protein [48][49][50][51][52][53][54]. Unlike GST and MBP, SUMO does not itself serve as a means for purification of fusion proteins; however, the His 6 in series with the SUMO tag has been established to facilitate purification of fusion proteins.…”
Section: Small Ubiquitin-related Modifier (Sumo)mentioning
confidence: 99%
“…When used as an N-terminal carrier protein during prokaryotic expression, SUMO promotes folding and structural stability, which leads to enhanced functional production compared to untagged protein [48][49][50][51][52][53][54]. Unlike GST and MBP, SUMO does not itself serve as a means for purification of fusion proteins; however, the His 6 in series with the SUMO tag has been established to facilitate purification of fusion proteins.…”
Section: Small Ubiquitin-related Modifier (Sumo)mentioning
confidence: 99%
“…One of the reasons for this result may be the effect of the SUMO peptide fusion in enhancing the solubility of viral recombinant proteins expressed in E. coli (Guerrero et al, 2015;Shafer et al, 1998;Zuo et al, 2005) Recombinant NP epitope prediction confirmed that most antigenic sites of this recombinant protein were conserved compared to the NP of homologous (H4N6) and heterologous (H1N1, H2N2, H3N2, H5N1, H6N7, and H9N2) AIV subtypes. In addition, some amino acid residue stretches predicted as rNP epitopes in this study, such as 71 to 96 and 290 to 353, have been previously confirmed as target epitopes of monoclonal antibodies to NP from AIV subtype H1N1 (Varich and Kaverin, 2004;Yang et al, 2008).…”
Section: Discussionmentioning
confidence: 82%
“…An approach used to circumvent this limitation is to increase the solubility of expressed recombinant proteins through the use of vectors harboring peptide and tags, such as the small ubiquitin-like modifier (SUMO) peptide (Guerrero et al, 2015;Zuo et al, 2005). Such vectors have been constructed for cloning and expression in E. coli systems, but to date this approach has not been used for the expression of AIV proteins.…”
Section: Introductionmentioning
confidence: 99%
“…SUMO proteases remove SUMO from proteins by cleaving the C-termini of SUMO (-GGATY) in yeast to the mature form (-GG) or deconjugating it from lysine side chains (Li and Hochstrasser, 1999;2000). Proteins such as SARS virus protein (Zuo et al, 2005), MMP13 (Marblestone et al, 2006), EGF (Su et al, 2006), metallothionein (Huang et al, 2009), and KGF2 (Wu et al, 2009) have been successfully expressed and purified using this fusion strategy. Recently, Liu et al (2008) have created an R64T, R71E double mutant of yeast SUMO (smt3), termed SUMOstar, which is not recognized by native desumoylases .…”
Section: Construction Of Transfer Vectormentioning
confidence: 99%